A new genus and species of vespertilionid bat from the Indomalayan Region - Ruedi, Manuel (J Mammal, 2018)
Bats belonging to the subfamily Vespertilioninae are diverse and cosmopolitan, but their systematic arrangement remains a challenge. Previous molecular surveys suggested new and unexpected relationships of some members compared to more traditional, morphology-based classifications, and revealed the existence of taxonomically undefined lineages. We describe here a new genus and species corresponding to an enigmatic lineage that was previously identified within the genus Eptesicus in the Indomalayan Region. Phylogenetic reconstructions based on mitochondrial and nuclear genes relate the new taxon to Tylonycteris and Philetor, and show that specimens associated with this new genus represent 2 genetically distinct species. Although little is known about their ecology, locations of capture and wing morphology suggest that members of this new genus are tree-dwelling, open-space aerial insect predators. The new species has only been documented from Yok Don National Park in Vietnam, so its conservation status is uncertain until more surveying methods target the bat fauna of the dipterocarp forest in Southeast Asia.